Mapping the interplay of technical, economic, social, and environmental dimensions in food-sector wastewater reclamation: a systematic literature review - Mat Yusoff, Nabiilah; Suleiman, Norhidayah; Abdul-Hamid, Asma Qamaliah; Ali, Mohd Helmi (Academic Press, 2025)
Water is an indispensable resource in the food sector, playing a critical role in production processes. However, wastewater generation presents significant challenges, including the opportunity to recover valuable resources. Wastewater reclamation within the food sector has emerged as a crucial practice, offering potential benefits such as economic efficiency, societal well-being, technological advancement, and environmental preservation. This study conducts a systematic literature review (SLR) to consolidate fragmented research and provide a comprehensive overview of the current state of wastewater reclamation in the food sector. This review analyses 51 articles published between 2013 and 2025, sourced from the Scopus and Web of Science database. The review synthesizes existing research and organizes it into two primary dimensions: (1) the factors influencing the implementation of wastewater reclamation in the food industry and (2) the benefits and barriers associated with these practices. The study classifies these factors into five key domains: water consumption, water generation, technological innovation, wastewater utilization, and reuse practices. It further highlights the crucial role of technical considerations in addressing barriers and maximizing the benefits of wastewater reclamation. The paper contributes to the scientific understanding of wastewater reclamation by proposing five key propositions that form a novel interconnected theoretical framework. This framework offers new insights into the complex dynamics of wastewater management in the food sector and identifies emerging trends. The study underscores the importance of aligning wastewater reclamation technologies with business objectives and encourages policymakers to implement robust environmental standards that facilitate sustainable practices.